Analysis of the Influence of Small and Medium Enterprises Entrepreneurship Development on the Adoption of E-Commerce - Reani Deswianita; Peggy Ratna Marlianingrum (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study was conducted to determine the effect of SME Entrepreneurship Development on e-commerce adoption at The North Jakarta Industry, Trade, Small and Medium Enterprises Sub-dept. Data were collected from 190 respondents who were participants in SME Entrepreneurship Development at the North Jakarta Industry, Trade, Small and Medium Enterprises Sub-dept. in 2023. The design of this study is associative causal using primary data obtained from questionnaires with analysis using linear regression analysis. The results of the study show that SME entrepreneurship development has a significant effect on e-commerce adoption. The findings show that SME actors who participate in SME entrepreneurship development training have not been helped in understanding how business goals should be achieved.